Two new species of Batrisodes Reitter from Shaanxi, China (Coleoptera: Staphylinidae: Pselaphinae) - Zhang, Wen-Xuan; Yin, Zi-Wei (Zootaxa, 2021)
Two new species of the genus Batrisodes Reitter, e.g., B. grandiceps sp. nov. and B. grossepunctatus sp. nov., are described from Shaanxi, central China. The two species are morphologically similar to each other in possessing similar cephalic modifications of the male, and the aedeagus with a well-developed endophallus.